An Emperor Travels around the Russian Empire Outskirts in the 1880s: As According to V.S. Obolenskii’s Diary - Olesya A. Plekh; Natalya V. Chernikova (RUDN Journal of Russian History, 2023)
Based on the materials from a previously unpublished source - the diary of Prince V.S. Obolenskii-Neledinskii-Meletskii, preserved in the Department of Written Sources of the State Historical Museum, the authors in their article consider the travels of Alexander III through the outlying territories of the Russian Empire in 1882-1888. The diary contains not only many details from the life of the imperial family and the court, but also information on the organization of official and unofficial trips of the emperor, which made it possible to trace the changes that took place in the ceremonial practice and the influence of modernization processes on the goals of the emperor's travels. There is presented through new information on the official visits of Alexander III to Poland (1884, 1886), Finland (1885), the Province of the Don Cossack Host (1887), Ukraine (1885) and the Caucasus (1888), as well as on private vacation trips to the Finnish skerries, the Principality of Łowicz and Livadia. The author shows that as inspection and study trips around Russia became a thing of the past, as ceremonial events came to the fore. The travels of Alexander III, continuing the line traced under Alexander II, were intended to establish a positive image of the monarch and emphasize the connection with his subjects. In the 1880s, visits to remote imperial residences for the purpose of recreation and entertainment became a regular occurrence, events which should be considered as an important part of the daily life of the imperial family.